TheInfluence of Using Short Video Towards the Students’ Speaking Skill at Grade VII of SMPN 22 Bandar Lampung - Dita Oktapiana (International Multidiciplinary Conference on Social Sciences (IMCoSS), 2015)
The main objective of this reseach was aimed to identify whether the use of short video was influence in improving the students’ speaking skill.Thepopulation was the first year students of SMPN 22 Bandar Lampung in academic year of 2014-2015 with a total number of 165 students. Out of this population, 54 students were taken as sample. There were two groups, each of which consisted of 27 students. One class became the experimental, while the other one became the control group. Different treatments were given to both groups, that was short video given to the experimental group while the control group taught by traditional teaching. The test of speaking was the instrument and then administered in two sections: pretest and posttest. The score obtained was analyzed by using t-test formula. The experimental data revealed two important results.First, adopting a technique of short video technique could significantly improve the students’ speaking skill because it was supported by sounds and pictures. The result obtained from experimental group revealed that short video performed better on the post test. Second, the final findings of this research were formulated. From the t-test calculation of the pre-test of experimental group was 1,416 and the post-test was 1,914. Whereas in control group the result of pre-test was 1,239 and the post-test was 1,522. The result of this study showed that the students taught by using short video technique got better ability. By calculating the scores of the t-Test, the result was Pvalue 1%= 2,68, Pvalue 5%= 2,01. Moreover, the t-Test value was 6,92.It is described clearly that the t-Test value was greater that p value. This meant that the application of short video technique was very effective. Therefore, it could be concluded that short video technique improved the students’ speaking achievement.